Vegetation response to restoration management of a blanket bog damaged by drainage and afforestation - Hancock, Mark H.; Klein, Daniela; Andersen, Roxane; Cowie, Neil R. (Applied vegetation science, 2018)
Questions: Does restoration management of a formerly afforested blanket bog lead to the vegetation, and the environmental conditions it indicates, becoming similar to intact bog? Location: A 147-ha blanket bog in Scotland's Flow Country, afforested in the 1980s but undergoing restoration since 1998. Methods: Vegetation in the restoration area was surveyed in nine, 1.6–6.4-ha plots, in 1998, 2003 and 2011. Each plot was matched to nearby plots that were either intact bog or remained afforested. Principal Response Curves were used to highlight the main axes of vegetation variation and test whether plant community trajectories in the restoration area differed from intact bog. The following restoration outcomes were assessed: floristic similarity to bog vegetation; and moisture, fertility and acidity, as inferred from vegetation using Ellenberg indicator values. Results: In the 6 years after restoration began, vegetation developed towards bog-like conditions. In the subsequent 8 years, overall vegetation change stalled, and spatial variability increased, reflecting diverging trajectories in wetter and drier parts of the site. Ellenberg's F-values implied significant re-wetting in the restoration area, reaching moisture levels similar to intact bog. Other restoration outcomes progressed in wetter microsites and areas (furrows and flat ground), but stalled in drier locations (plough-ridges and steeper slopes). Conclusions: Overall moisture conditions, as indicated by plants, have recovered. However, restoration progress has stalled in drier areas, where additional management may be needed. Long-term vegetation monitoring has helped clarify barriers to recovery and the management needed to overcome them. The value of such monitoring schemes in guiding restoration should be reflected in their wider implementation, within an adaptive management framework.